Cross country skiers and kayakers demonstrate similar decreases in VO2max at altitude - Roberts, A.; Martin, D.; Logan, P.; Daley, P.; Hahn, A.; Gore, C.; Spence, R.; Dixon, J. (1998)
The consistent reductions in VO2max at altitude in the different athletes confirm that this is an altitude related phenomenon, independent of the mode of activity. Such a reduction in VO2max at altitude would impose a limitation on training and performance, at least until acclimatisation could be effected. The reduction in SaO2 in both skiers and kayakers indicates that at altitude the O2 supply to the active muscles is a factor limiting VO2max.